PEMANFAATAN MEDIA DADU BERGAMBAR PADA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V DALAM MENYAJIKAN DATA - Ahmad Syaiful Fahry; Sekar Dwi Ardianti (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to improve the learning outcomes of fifth-grade students at SD Muhammadiyah 1 Kudus in mathematics, particularly in the competence of presenting data through the utilization of picture dice media. The research method employed is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of four stages: planning, action, observation, and reflection. The subjects were 18 fifth-grade students in the 2024/2025 academic year. Data were collected through observation, tests, interviews, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The results showed an improvement in students' learning outcomes from the pre-cycle, first cycle, to the second cycle. In the pre-cycle, the students’ mastery level was only 56%, increased to 72% in the first cycle, and reached 83% in the second cycle. The use of picture dice media proved effective in enhancing students' motivation, conceptual understanding, and learning outcomes in data presentation. Thus, concrete media like picture dice can serve as an innovative alternative to improve the quality of mathematics learning in elementary schools.